A LARGE MASS IN THE MANDIBLE IN AN EIGHT YEAR OLD CHILD - Gökhan Gürler; Serdar Yılmaz; Çağrı Delilbaşı; Merva Soluk Tekkesin (Selcuk Dental Journal)
Facial swellings in children may commonly arise from infection, jaw cysts or benign-malign tumors. Differential diagnosis should be handled considering onset of the symptoms, growth rate and child’s age. Fibro-osseous lesions are a group of lesions characterized by fibrosis and contain varying amounts of calcified tissue resembling bone, cement or both. Such lesions may cause enlargement and swelling in the jaws. Juvenile ossifying fibroma (JOF) is one of the fibro-osseous lesions usually seen in children and adolescents. It has an aggressive character with a high recurrence rate. Mandible is more affected than maxilla and psammomatoid type is more common than trabecular type histologically. Bone resection is generally preferred for the treatment due to nature of the tumor.